2016
DOI: 10.1039/c6ra20725a
|View full text |Cite
|
Sign up to set email alerts
|

CuO nanostructures of variable shapes as an efficient catalyst for [3 + 2] cycloaddition of azides with terminal alkyne

Abstract: CuO nanowires exhibited highest catalytic efficiency for the cycloaddition reaction between azide and terminal alkyne, featuring short reaction time, soft reaction conditions and complete regioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 93 publications
1
8
0
Order By: Relevance
“…Moreover, a small hump at 280 nm in the absorption spectrum of IPN1 could be attributed to ionic silver or charged clusters. This result confirmed the presence of embedded metal nanoparticles in the structure of hydrogels and is in agreement with previously published papers [35,36,37].…”
Section: Resultssupporting
confidence: 93%
“…Moreover, a small hump at 280 nm in the absorption spectrum of IPN1 could be attributed to ionic silver or charged clusters. This result confirmed the presence of embedded metal nanoparticles in the structure of hydrogels and is in agreement with previously published papers [35,36,37].…”
Section: Resultssupporting
confidence: 93%
“…46 For UV-vis spectrum of CuO-rGO nanocomposites, it is observed that the peak in GO spectrum at 230 nm is shied to 256 nm due to the reduction GO sheet and the characteristic peak of CuO nanoparticles appeared at 375 nm. 46,47 Also, the characteristics peak of AgNPs appeared at 400 nm in the spectrum of Ag-rGO and Ag/CuO-rGO nanocomposites which conrms the presence of AgNPs on GO surface. 48 The structures and phase composition of all prepared samples were examined by using XRD measurements and the corresponding pattern is shown in Fig.…”
Section: Resultsmentioning
confidence: 95%
“… 48 For CuO-rGO and Ag/CuO-rGO nanocomposites, the diffraction peaks observed at 2 θ values of 33, 35, 38, 48.7, 53.5, 58.3, 61.7, and 67.9 correspond to (110), (111), (200), (202), (020), (021), (113), and (220) planes, respectively which are characteristic peaks of the monoclinic structure of CuO. 47 Additionally for Ag-rGO and Ag/CuO-rGO nanocomposites, the XRD shows two peaks at 2 θ = 38.3°, 44.2° correspond to the (111), (200) planes, respectively which are characteristic of the face-centered cubic structure of AgNPs. 48 Also Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Because of the presence of Cu-ablated specious in the turquoise phase of the target after the laser ablation of the turquoise phase (Figures S5a and c), the absorption spectrum for this sample was intensified in the UV region. The UV absorption of Cu compounds usually was in the visible region and changed to the UV region with quantum confinement effect enhancement . In addition, UV absorption of the sample was observed because of the direct-charge transfer transition of O 2– 2p → Fe 3+ 3d of α-Fe 2 O 3 in the turquoise phase-ablated species.…”
Section: Resultsmentioning
confidence: 99%